Relações de poder e o luteranismo em Santa Cruz do Sul – século XIX / Power relations and Lutheranism in Santa Cruz do Sul - 19th Century - Radünz, Roberto; Vogt, Olgário Paulo (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2013)
A história do luteranismo no sul do Brasil está associada à vinda dos imigrantes alemães no século XIX. As primeiras comunidades que surgiram em solo gaúcho tiveram como característica marcante uma profunda autonomia. Sem vínculos com a Igreja na Alemanha e sem sínodos, os colonos luteranos construíram suas comunidades com vistas a atender as necessidades sócio-religiosas. Cada comuna tinha sua diretoria que era responsável por gerir os negócios da igreja. Essa relação horizontal de poder, onde as decisões eram tomadas em assembleia, sempre foi reforçada como uma característica dos luteranos da igreja da imigração. O presente artigo discute essa imagem positivada apresentando um caso exemplar que evidencia que as tensões e os conflitos eram muito mais comuns do que a historiografia ligada ao tema tem apontado. Abstract <span style="font-size: 10.0pt; line-height: 115%; font-family: ";Bookman Old Style";,";serif";; mso-fareast-font-family: Calibri; mso-bidi-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: AR-SA; mso-bidi-language: AR-SA;" lang="EN-US">The history of Lutheranism in the south of Brazil is associated with the coming of German immigrants in the 19th century. The first communities to appear in this Brazilian region had as an outstanding characteristic a deep autonomy. With no bonds with the church in Germany and no synods, the Lutheran settlers built their communities aiming to meet their socio-religious necessities. Each commune had its own direction that was responsible for managing the church businesses. This horizontal relation of power, where the decisions were taken in assembly, was always enhanced as a characteristic of the Lutherans who belonged to the immigration church. This paper discusses this positivated image showing an exemplar case which highlights that the stresses and conflicts were even more common than the historiography dedicated to this subject has pointed out.